New financial management system for Iran public health sector: A qualitative study - Masoud Abolhallaj; Mehdi Jafari; Hesam Seyedin; Masoud Salehi; Arefeh Pourtaleb; Keyvan Rahmani; Seyede-Elahe Hosseini (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Financial management system acts as a driving force and the first important principle of health sector reform. This study aimed to prepare a framework for new financial management system in Iran health sector. MATERIALS AND METHODS: This qualitative study was conducted by content analysis approach and 15 key informant participants selected through purposive sampling consisted of three minsters of Ministry of Health and Medical Education (MOHME), three vice-chancellors in the Center of Resource Development and Management, Two members of the Health Assembly of the Islamic Consultative, four Medical Sciences university's presidents, and three managers in Budgeting and performance Monitoring Center of MOHME in 2017. Data were collected through semi-structured interviews and they were analyzed using Atlas T6 software. RESULTS: Six main themes were emerged as follow: "legal reform," "removing barriers to set up accrual accounting," "cost price calculation," "operational planning and budgeting," "human resources' organization, recruitment, and moderation," and "financial system output utilization (management accounting techniques) as the base for evidence-based policymaking and decision-making practices." CONCLUSION: Any efforts for improving the current situation and reducing of mentioned limitations could be useful in providing required space for future phases of reforms and calculation of unit cost, operational budgeting, and management of cost and productivity. This can be achieved through an integrated system of recording and producing standard and accrual financial information. Furthermore, changing the accounting process and the financial system that complies with one single encoding in the country is a key issue.